Outcomes of 1‐MCP combined with aerosolization of ε‐polylysine antimicrobials on storage quality of flat peach. Issue 6 (29th October 2022) - Shao, Limei; Jia, Xiaoyu; Zhang, Peng; Li, Chunyuan; Li, Jiangkuo
Abstract: Fruit decay and deterioration in overall quality are the main problems of preserving peaches after they are harvested. In this article, the outcomes of 1‐MCP combined with polylysine atomization on Xinjiang flat peaches were evaluated. Distilled water atomization treatment, 1, 000 mg/L polylysine atomization treatment for 10 min and 1, 000 mg/L polylysine atomization treatment for 20 min were employed. Results showed that the combined treatment using 1‐MCP and polylysine helped to delay the fruit decay rate, respiration, ethylene production, respiration intensity, organic acids, soluble solids, hardness, and microorganisms. Furthermore, reactive oxygen metabolism of O 2− and OH − was inhibited. A combined treatment can effectively improve the antioxidant capacity during almond storage, and thus improve shelf life. Therefore, 1‐MCP combined with polylysine atomization treatment is necessary to control fruit rotting and to extent the storage life. Abstract : 1‐MCP in combination with aerosolized ɛ‐PL increased antioxidant capacity of flat peach. Aerosolized ɛ‐PL could inhibit postharvest rot on flat peach.